Examining the Values and Principles of Agile Construction Management in Iraqi Construction Projects (Journal of Engineering, 2018)
The avoidance of failure in construction projects is not an easy task, which makes the failure of the construction project to achieve its objectives a major problem experienced by all countries in the world, especially Iraq. Where nearly two-thirds of the construction projects in the world have been suffered by significant problems as an increase in the cost of the project, delay in the specified duration for execution, and stopping the project. Therefore it is required to study and apply new methods for managing the construction project to ensure its success and achieve its objectives. The aim of this study is to study the Agile project management method and its impact on the construction project. In addition, to identify the values and principles of Agile project management, which can be applied in the Iraqi construction industry to be adopted it as a new method to manage the construction projects in Iraq. The researcher reviewed the relevant literature to define the method of Agile project management and its methods and impact on the construction project. Then, the researcher conducted a questionnaire survey of a sample of engineers' experts who work in four main parties in the construction project: (beneficiary, supervising, designer, and contractor). The results of this survey showed that it is possible to apply the four values of Agile project management for managing the Iraqi construction projects, and can apply eleven of the twelve principles of Agile project management for managing the Iraqi construction projects.